A Probabilistic Atlas of the Pineal Gland in the Standard Space - Razavi, Foroogh; Raminfard, Samira; Kalantar Hormozi, Hadis; Sisakhti, Minoo; Batouli, Seyed Amir Hossein (Frontiers in Neuroinformatics, 2021)
Pineal gland is a midline structure of the brain, and is considered as the main part of the epithalamus. There are numerous reports on the facilitatory role of this area for brain function; hormone secretion and its role in sleep cycle are the major reports. However, rare reports are available on the direct role of this structure in brain cognition and in information processing. One suggestion for the limited number of such studies is the lack of a standard atlas for the pineal gland; none of the available MRI templates and atlases has provided parcellations for this structure. In this study, we used the three-dimensional T1-weighted MRI data of 152 healthy young volunteers, and provided a probabilistic map of the pineal gland in the standard MNI space. The methods included collecting data using a 64-channel head coil on a 3Tesla Prisma MRI Scanner, manual delineation of the pineal gland by two experts, and robust template and atlas construction algorithms. This atlas is freely accessible, and we hope importing this atlas in the well-known neuroimaging software packages would help to identify other probable roles of the pineal gland in brain function. It could also be used to study pineal cysts, for volumetric analyses, and to test any association between the structure of the pineal gland and the cognitive abilities of the human.